Strong-field approximation for analytical calculation of the residual current density excited by gas ionization with an intense two-color laser pulse - Romanov, A.A.; Silaev, A.A.; Vvedenskii, N.V. (Вопросы атомной науки и техники, 2015)
On the basis of analytical solution of the time-dependent Schrödinger equation the excitation of residual current density (RCD) in a gas ionized by two-color laser pulse is studied. We find general analytical expression for the RCD for arbitrary values of the Keldysh parameter, which coincides with the semiclassical calculations in the case of tunneling regime of ionization. На основі аналітичного розв’язку нестаціонарного рівняння Шредингера досліджується збудження залишкової густини струму в газі, що іонізований інтенсивним біхроматичним лазерним імпульсом. Знайдено загальний аналітичний вираз залишкової густини струму для довільних значень параметру Келдиша, який співпадає з результатами напівкласичних розрахунків при тунельному режимі іонізації. На основе аналитического решения нестационарного уравнения Шрёдингера исследуется возбуждение остаточной плотности тока в газе, ионизируемом интенсивным бихроматическим лазерным импульсом. Найдено общее аналитическое выражение остаточной плотности тока для произвольных значений параметра Келдыша, которое совпадает с результатами полуклассических расчетов при туннельном режиме ионизации.